Evaluation of Ischemia-Modified Albumin and Fibrinogen in Relation with High-Sensitive C-reactive Protein in Diabetic Foot Ulcers - Afrah, Haleemath; Sridhar, Reshma; Sushith, Sushith; Balakrishna, Prathima; Hanumanthappa, M; Srinivasan, Mukund; Ramarajan, Madan (Journal of Diabetes and Endocrine Practice, 2020)
Context: Diabetic foot ulcer (DFU) is one of the most dreaded complication of diabetes which often affects the morbidity and mortality of a diabetic. Biomarkers are required for follow-up of these patients to prevent further complications to the affected limb. Aim: The aim of this study is to evaluate ischemia-modified albumin (IMA), fibrinogen in relation with high sensitive-C-reactive protein (hs-CRP) in patients with DFUs. Methods: a hospital-based cross-sectional study was carried out among 30 patients with DFU admitted in the surgery department of tertiary care teaching hospital. The duration of the study was 2 months. Serum IMA, hs-CRP, and plasma fibrinogen levels were measured. Results: The present study has demonstrated that IMA levels (P < 0.05) and fibrinogen levels (P < 0.05) are statistically significantly elevated in patients with DFU and had significant correlation with albumin and hs-CRP (P < 0.05). Conclusions: The use of IMA, hs-CRP, and fibrinogen may be incorporated during the follow-up of type 2 diabetes mellitus patients and may probably prevent the development of DFU and also possibly prevent lower limb amputation. Further studies with a larger number of patients with DFU are necessary to reach a definitive judgment.
Keywords: Diabetic foot; fibrinogen; high-sensitive C-reactive protein; ischemia-modified albumin